THE MULTIFUNCTION MEASURING CONVERTER FOR MONITORING OF LIQUID TECHNOLOGICAL MEDIA - R. I. Vorobey; O. K. Gusev; A. L. Zharin; Yu. G. Kuzminsky; A. I. Svistun; A. K. Tyavlovsky; K. L. Tyavlovsky; S. V. Shilko (Приборы и методы измерений)
The multifunctional sensor of solution type and concentration in a technological pipeline is developed on a basis of the methodology of measurements of parameters of objects with indefinite states. Theoretical and experimental results demonstrate that both concentration measurement and solution type definition modes can be realized in a single one-element sensor. Adaptive control of excitation regimes of sensor’s electrodes is needed to ensure single-signal measurements. Algorithms of measurements and construction of a measuring device for multiparameter measurements of liquid media properties utilizing adaptive technique of measurements of parameters of objects with indefinite states are developed.